Development of a Community Complaint Information System to Support the Realization of a Smart Village in Sibetan - Juliana Eka Putra, I Gede; I Made Wahyu Baskara (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2025)
A computerized (digital) village is one of the key initiatives introduced by public authorities to support the sustainable development of rural areas across the Republic of Indonesia. One of the primary objectives of a Digital Village is to disseminate information rapidly, accurately, and efficiently to local communities while promoting transparency and public participation. Sibetan Village is among those committed to becoming a digital village through the integration of information and communication technologies into its governance systems. However, in developing a local complaints website, the testing process must strictly adhere to the village’s expected quality standards to ensure usability, reliability, and effectiveness. Villages are widely encouraged to leverage data-driven innovations to enhance administrative processes, improve public service delivery, and foster inclusive community engagement. In Sibetan, one such initiative is the development of a web-based Regional Complaints Information System, designed to facilitate the submission of inquiries and complaints from the public, enabling faster responses by village authorities. The system was designed using the Waterfall method to accommodate user requirements. The outcome of this research is the user interface design of the Sibetan Village community complaints website.